2014
DOI: 10.3989/ajbm.2381
|View full text |Cite
|
Sign up to set email alerts
|

First record of <em>Caulerpa cylindracea</em> (Caulerpaceae, Chlorophyta) in Andalusia (Southern Spain)

Abstract: Three different species of Caulerpa (Caulerpaceae, Chlorophyta) cooccur in the Mediterranean Sea: two of them are found at the centraleastern basin and are typically considered non aggressive components of the Lessepsian flora [(C. chemnitzia (Esper) J.V. Lamouroux and C. racemosa var. lamourouxii (Turner) Weber-van Bosse f. requienii (Montagne) Weber van Bosse)]; a third taxon, C. cylindracea Sonder has aggressively expanded its range since its first observation in 1990, and it is nowadays reported from nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In the eastern Iberian Peninsula, C. cylindracea recently spreads over the coastal area between Catalonia (García et al 2015) and Andalusia (Altamirano et al 2014), where it shows a similar distribution pattern to that reported in other Mediterranean regions (Verlaque et al 2003, Klein andVerlaque 2008). Thus, it thrives in shallow subtidal waters and in deep subtidal habitats beyond 30 m depth.…”
Section: Introductionsupporting
confidence: 67%
“…In the eastern Iberian Peninsula, C. cylindracea recently spreads over the coastal area between Catalonia (García et al 2015) and Andalusia (Altamirano et al 2014), where it shows a similar distribution pattern to that reported in other Mediterranean regions (Verlaque et al 2003, Klein andVerlaque 2008). Thus, it thrives in shallow subtidal waters and in deep subtidal habitats beyond 30 m depth.…”
Section: Introductionsupporting
confidence: 67%
“…Under this caveat, it is noticeable that in Almerian localities where the two Asparagopsis OTUs co‐occur, the subtidal communities are additionally affected by the invasive Caulerpa cylindracea (Altamirano et al. ). Despite the lack of impact assessments for these invasive OTUs from Almeria, our overall impression during this work was one of biotic homogenization and species richness decline (M. Altamirano, J.…”
Section: Discussionmentioning
confidence: 99%
“…The species could be the first observation in the area. The species is a native of Australia and has spread its invasion to the Canary Islands [35], Great Barrier Reef [36] and the Mediterranean [37].…”
Section: Resultsmentioning
confidence: 99%